Predicting autologous hamstring graft diameter and finding reliable measurement levels in the Zhuang population using preoperative ultrasonography - Huang, Xiao-Li; Zheng, Hong-Yu; Shi, Ze-Feng; Yang, Hui-Hui; Zhang, Bing; Yang, Xiao-Chun; Wang, Hong; Tan, Ru-Xin (Frontiers in Physiology, 2022)
Purpose: To evaluate the feasibility of using ultrasonography to preoperatively predict the autologous hamstring graft diameter for anterior cruciate ligament (ACL) reconstruction in the Zhuang population and determine a reliable measurement level using ultrasound. Methods: Twenty-four Zhuang patients who were scheduled for ACL reconstruction using four-strand semitendinosus tendon (ST) and gracilis tendon (GT) (4S-STG) autografts were included in this study. Ultrasonographic examinations of the ST and the GT on the damaged side were conducted before the operation. We recorded the transverse diameter (TD), anterior–posterior diameter (APD), cross-sectional area (CSA), and perimeter (P) of the tendons. The measurements were obtained from two levels of the tendons: the widest point of the medial femoral epicondyle (level 1) and the myotendinous junction of the sartorius (level 2). We also calculated the combined (ST + G) TD, APD, CSA, and P values. Then, we obtained the intraoperative measurements. The correlation between the ultrasonic and intraoperative measurements was analyzed, and the advantages of the ultrasonic measurements at the two different levels were compared. Results: When we measured at level 1, we found that the preoperative CSA of the GT (P-GCSA) (r = 0.499, p < 0.05) and the preoperative combined APD (r = 0.415, p < 0.05) were correlated with the diameter of the 4S-STG autograft. The area under the P-GCSA curve was 0.801 (p < 0.05). A P-GCSA of 8.5 mm² could be used to predict a 4S-STG autograft diameter of ≥8 mm with a sensitivity of 61.1% and specificity of 83.3%. However, there was no correlation between the ultrasonic and intraoperative measurements at level 2. Conclusions: Preoperative ultrasound can be used to predict the sufficient diameter of 4S-STG autografts when considering patients from Zhuang who are undergoing ACL reconstruction. The ultrasonic measurement should be obtained at the widest point of the medial femoral epicondyle.